THE IMPLEMENTATION OF MANAGEMENT BASED ON SPIRITUAL QUOTIENT TO DEVELOP STUDENT’S RELIGIOUS CHARACTER AT SMAN 1 GROGOL KEDIRI - Amalia, Husna (EDUKASI: Jurnal Pendidikan Islam, 2018)
Education is not only the effort to develop cognitive aspect of student but also it tries to develop aspect of affective and psycomotor. Students are expected to have good behavior that is shown by strong spirituality. In developing student’s religious character,  school implement the management based on spiritual quotient to help students do religious values. The development of religious character for student is important because in this era there are many immoralities that caused by some factors especially in their environment. This research focused on (1) To describe the implementation of management based on spiritual quotient to develop student’s religious character at SMAN 1 Grogol Kediri. (2) To describe the obstacles of the implementation of management based on spiritual quotient to develop student’s religious character at SMAN 1 Grogol Kediri. This research use descriptive qualitative approach to describe and interpret two cases above based on real phenomena in the field. The researcher as a partisipative observer to collect data at SMAN 1 Grogol Kediri. The method of collecting data include observation, interview, and documentation. Then, the technique of analysis data use reduction and taking conclusion. The result of research shown that school implement management based on spiritual quotient through some religious programs that is introduced in student’s orientation, learning process in the class that is intregated by character value, and the existence of SKI and subject character of nation. The series of activity in the school can make them to have habitual to implement religious value, therefore it can develop their religious character. In implementing mangement based on Spiritual Quotient also appear some obstacles, therefore school commitee efforts to do straightening for achieving better result.